Design and Fabrication of Patient-Specific Orthotic Devices through 3D Scanning, Generative Design, and Additive Manufacturing (Jóvenes en la Ciencia, 2025)
Customizing orthopedic splints poses significant clinical and technological challenges, especially in achieving optimal anatomical and functional adaptation for each patient. This study aimed to design, fabricate, and validate a personalized splint through a digital workflow incorporating 3D scanning, generative design, finite element analysis, and 3D printing with biocompatible polymers. An exploratory mixed-methods approach was used to document each stage and assess both device performance and user acceptance. The resulting splint met structural and anatomical requirements, exhibiting maximum deformations of 0.619 mm (PLA) and 0.853 mm (PETG) with safety factors exceeding 4. Total manufacturing time was 6 hours and 50 minutes, withoptimized material use resulting in a final cost of approximately $30 MXN. The device was perceived as lightweight and comfortable, and users showed a clear preference over conventional plaster casts. These findings highlight the potential of digital tools and 3D printing for efficient, patient-specific orthosis fabrication and support their adoption in educational and clinical environments.